PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI (STUDI KASUS PENELITIAN PADA MAHASISWA AKTIF INSTITUT STIAMI PUSAT) - Agus Setiawan; Abbas Mansyur; Supriyono Supriyono (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The phenomenon in this research is the significant increase in sales of Xiaomi smartphones in Indonesian Market that occurred in 2018, succeeding in acquising a market share up to 25%. The number increased dramatically, where in the same period the in previous year Xiaomi's market share was only 3%, then the problem was whether Product Price and Quality affected the purchasing decision of Xiaomi smartphones in Indonesia.This research uses quantitative descriptive method. The variables in this study consisted of two independent variables namely Price, Product Quality and one dependent variable, namely purchasing decisions. All research variables will be formulated into a questionnaire in the form of a statement and use a Likert scale with 5 level choices, namely strongly agree, agree, disagree, disagree and strongly disagree. The analytical method used to solve the problem in this study is SPSS application, namely the Multiple Regression Analysis Test and the Statistical T Test and F Test.                              The results of the initial analysis conducted showed that the indicators used were valid and reliable to measure the existing variables. The price influence magnitude of 0.585 or 58.5% on the Purchasing Decision, while the remaining 41.5% is caused by other factors not examined in this study. the influence of Product Quality results obtained by 0.657 or 65.7% of the Purchasing Decision, while the remaining 34.3 caused by other factors not examined in this study. The results of the subsequent analysis showed that the price variable and product quality variables simultaneously (together) affected the purchase decision of 72.8%. While the remaining 27.2% is influenced by other variables outside this regression equation or variables haven’t examined.